Electron beam-induced deposition of platinum from Pt(CO)2Cl2 and Pt(CO)2Br2 - Mahgoub, Aya; Lu, Hang; Thorman, Rachel M.; Preradovic, Konstantin; Jurca, Titel; McElwee-White, Lisa; Fairbrother, Howard; Hagen, Cornelis W. (Beilstein Journal of Nanotechnology, 2020)
Two platinum precursors, Pt(CO)2Cl2 and Pt(CO)2Br2, were designed for focused electron beam-induced deposition (FEBID) with the aim of producing platinum deposits of higher purity than those deposited from commercially available precursors. In this work, we present the first deposition experiments in a scanning electron microscope (SEM), wherein series of pillars were successfully grown from both precursors. The growth of the pillars was studied as a function of the electron dose and compared to deposits grown from the commercially available precursor MeCpPtMe3. The composition of the deposits was determined using energy-dispersive X-ray spectroscopy (EDX) and compared to the composition of deposits from MeCpPtMe3, as well as deposits made in an ultrahigh-vacuum (UHV) environment. A slight increase in metal content and a higher growth rate are achieved in the SEM for deposits from Pt(CO)2Cl2 compared to MeCpPtMe3. However, deposits made from Pt(CO)2Br2 show slightly less metal content and a lower growth rate compared to MeCpPtMe3. With both Pt(CO)2Cl2 and Pt(CO)2Br2, a marked difference in composition was found between deposits made in the SEM and deposits made in UHV. In addition to Pt, the UHV deposits contained halogen species and little or no carbon, while the SEM deposits contained only small amounts of halogen species but high carbon content. Results from this study highlight the effect that deposition conditions can have on the composition of deposits created by FEBID.
Keywords: energy-dispersive X-ray spectroscopy (EDX); focused electron beam-induced deposition (FEBID); nanofabrication; platinum precursors; scanning electron microscopy (SEM); thermogravimetric analysis (TGA)

(untitled) - Hagen, C. W. (Appl. Phys. A: Mater. Sci. Process., 2014)

(untitled) - Randolph, S. J.; Fowlkes, J. D.; Rack, P. D. (Crit. Rev. Solid State Mater. Sci., 2006)

(untitled) - van Dorp, W. F.; Hagen, C. W. (J. Appl. Phys., 2008)

(untitled) - Huth, M.; Porrati, F.; Schwalb, C.; Winhold, M.; Sachser, R.; Dukic, M.; Adams, J.; Fantner, G. (Beilstein J. Nanotechnol., 2012)

(untitled) - Miyazoe, H.; Utke, I.; Michler, J.; Terashima, K. (Appl. Phys. Lett., 2008)

Nanofabrication Using Focused Ion and Electron Beams : Principles and Applications - Utke, I.; Moshkalev, S.; Russell, P. (Oxford University Press, Incorporated, 2012)

Advances in Imaging and Electron Physics - Silvis-Cividjian, N.; Hagen, C. W. (Electron‐Beam–Induced Nanometer‐Scale Deposition, 2006)

(untitled) - Mulders, J. J. L.; Belova, L. M.; Riazanova, A. (Nanotechnology, 2010)

(untitled) - Mulders, J. J. L. (Nanofabrication, 2014)

Low-Energy Electrons: Fundamentals and Applications - Ingólfsson, O. (Jenny Stanford Publishing, 2019)

(untitled) - Mulders, J. J. L.; Veerhoek, J. M.; Bosch, E. G. T.; Trompenaars, P. H. F. (J. Phys. D: Appl. Phys., 2012)

(untitled) - Utke, I.; Hoffmann, P.; Dwir, B.; Leifer, K.; Kapon, E.; Doppelt, P. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2000)

(untitled) - Brintlinger, T.; Fuhrer, M. S.; Melngailis, J.; Utke, I.; Bret, T.; Perentes, A.; Hoffmann, P.; Abourida, M.; Doppelt, P. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2005)

(untitled) - Spencer, J. A.; Rosenberg, S. G.; Barclay, M.; Wu, Y.-C.; McElwee-White, L.; Howard Fairbrother, D. (Appl. Phys. A: Mater. Sci. Process., 2014)

(untitled) - Ferreira da Silva, F.; Thorman, R. M.; Bjornsson, R.; Lu, H.; McElwee-White, L.; Ingólfsson, O. (Phys. Chem. Chem. Phys., 2020)

(untitled) - Thorman, R. M.; Jensen, P. A.; Yu, J.-C.; Matsuda, S. J.; McElwee-White, L.; Ingólfsson, O.; Fairbrother, D. H. (J. Phys. Chem. C, 2020)

(untitled) - Spencer, J. A.; Brannaka, J. A.; Barclay, M.; McElwee-White, L.; Fairbrother, D. H. (J. Phys. Chem. C, 2015)

(untitled) - Cipriani, M.; Thorman, R. M.; Brewer, C. R.; McElwee-White, L.; Ingólfsson, O. (Eur. Phys. J. D, 2019)

(untitled) - Wnorowski, K.; Stano, M.; Matias, C.; Denifl, S.; Barszczewska, W.; Matejčík, Š. (Rapid Commun. Mass Spectrom., 2012)

(untitled) - Rosenberg, S. G.; Barclay, M.; Fairbrother, D. H. (J. Phys. Chem. C, 2013)

(untitled) - Spencer, J. A.; Barclay, M.; Gallagher, M. J.; Winkler, R.; Unlu, I.; Wu, Y.-C.; Plank, H.; McElwee-White, L.; Fairbrother, D. H. (Beilstein J. Nanotechnol., 2017)

(untitled) - Spencer, J. A.; Wu, Y.-C.; McElwee-White, L.; Fairbrother, D. H. (J. Am. Chem. Soc., 2016)

(untitled) - Bagnoli, F.; Amico, D. B. D.; Calderazzo, F.; Englert, U.; Marchetti, F.; Herberich, G. E.; Pasqualetti, N.; Ramello, S. (J. Chem. Soc., Dalton Trans., 1996)

(untitled) - Calderazzo, F. (J. Organomet. Chem., 1990)

(untitled) - Bagnoli, F.; Belli Dell'Amico, D.; Calderazzo, F.; Englert, U.; Marchetti, F.; Merigo, A.; Ramello, S. (J. Organomet. Chem., 2001)

(untitled) - Faust, M.; Enders, M.; Bruns, M.; Bräse, S.; Gao, K.; Seipenbusch, M. (Surf. Coat. Technol., 2013)

(untitled) - Fowlkes, J. D.; Winkler, R.; Lewis, B. B.; Fernández-Pacheco, A.; Skoric, L.; Sanz-Hernández, D.; Stanford, M. G.; Mutunga, E.; Rack, P. D.; Plank, H. (ACS Appl. Nano Mater., 2018)

(untitled) - Winkler, R.; Lewis, B. B.; Fowlkes, J. D.; Rack, P. D.; Plank, H. (ACS Appl. Nano Mater., 2018)

(untitled) - Fowlkes, J. D.; Rack, P. D. (ACS Nano, 2010)

(untitled) - Utke, I.; Hoffmann, P.; Melngailis, J. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2008)

(untitled) - Mehendale, S.; Mulders, J. J. L.; Trompenaars, P. H. F. (Nanotechnology, 2013)

(untitled) - Campbell, J. L.; Maxwell, J. A.; Papp, T.; White, G. (X-Ray Spectrom., 1997)

(untitled) - Warneke, Z.; Rohdenburg, M.; Warneke, J.; Kopyra, J.; Swiderek, P. (Beilstein J. Nanotechnol., 2018)

(untitled) - Geier, B.; Gspan, C.; Winkler, R.; Schmied, R.; Fowlkes, J. D.; Fitzek, H.; Rauch, S.; Rattenberger, J.; Rack, P. D.; Plank, H. (J. Phys. Chem. C, 2014)

(untitled) - Shawrav, M. M.; Taus, P.; Wanzenboeck, H. D.; Schinnerl, M.; Stöger-Pollach, M.; Schwarz, S.; Steiger-Thirsfeld, A.; Bertagnolli, E. (Sci. Rep., 2016)

(untitled) - Rohdenburg, M.; Boeckers, H.; Brewer, C. R.; McElwee-White, L.; Swiderek, P. (Sci. Rep., 2020)

(untitled) - Schmidt, F.; Swiderek, P.; Bredehöft, J. H. (ACS Earth Space Chem., 2019)